Multi-strain probiotics: functions, effectiveness and formulations for aquaculture applications - Puvanasundram, Puvaneswari; Chou, Min Chong; Sabri, Suriana; Yusoff, Md. Sabri; Murni, Karim (Elsevier, 2021)
Probiotics application in aquaculture has been a common practice over the last decade whereby this microbial derivate is used in the form of single or multi-strain probiotics (MSP). Multi-strain probiotics provide more benefits to aquatic organisms as it provides synergistic effect in contrast to the use of a single-strain probiotic (SSP). The effectiveness of MSP is due to the positive interrelationship or synergism among strains which leads to symbiosis. Compatibility between strains plays a major role to avoid antagonism which might lead to detrimental effect on host. The composition of commercial probiotic in the market which claims to have various benefits on host usually consists of MSP. One of the main benefits of MSP is inhibition of various marine and freshwater pathogens by increasing survival rate of host. The concept of MSP is also largely used in aquaculture to enhance non-specific immunity of host in terms of innate and adaptive immune response. The improvement in growth parameter including increased weight gain, specific growth rate, and protein efficiency ratio were also commonly observed in MSP fed host. Some of the criteria required in MSP formulations are safety aspect and origin of strain, in-vitro screening assay to select compatible strains as well as methods of administration to host. The selection of MSP should be based on factors such as inter-species inhibition and the effectiveness of the MSP as a consortium. There is a scarcity of research focusing on the mechanism of MSP and the interrelationship among strains which necessitates future research in this area. Overall, this review addressed the potential of MSP as a consortium focusing on the interaction between species, its functions, effectiveness, various aspect in formulating a MSP as well as gaps of existing knowledge in this area that could be considered for future research.